The Chemistry, Pharmacological and Therapeutic Applications of Asparagus racemosus- A Review - Velavan, S.; Nagulendran, KR.; Mahesh, R.; Begum, V. Hazeena (Pharmacognosy Reviews)
Medicinal plants are the nature’s gift to human being to make disease free healthy life. It plays a vital role to preserve our health. India is one of the most medico-culturally diverse countries in the world where the medicinal plant sector is part of a time-honored tradition that is respected even today. Medicinal plants are believed to be much safer and proved elixir in the treatment of various ailments. In our country more than two thousand medicinal plants are recognized. Asparagus racemosus Willd. (Asparagaceae) is an important medicinal plant of tropical and subtropical India. Its medicinal usage has been reported in the Indian and British Pharmacopoeias and in traditional systems of medicine such as Ayurveda, Siddha and Unani. A. racemosus has been described as a rasayana herb and has been used extensively as an adaptogen to increase the non-specific resistance of organisms against a variety of stresses. Besides use in the treatment of diarrhoea and dysentery, the plant also has potent antioxidant immunostimuulant, anti-dyspepsia and antitussive effects. The present article includes the detailed exploration of pharmacological properties of A. racemoses is an attempt to provide a direction for further research.
Keywords: Asparagus racemosus; Phytochemicals; Pharmacological action; Polyherbal formulation